Educational Effectiveness of Catholic Schools in Poland Based on the Results of External Exams - Cichosz, Wojciech (Religions, 2023)
Church education boasts a rich history of achievements. European church education (referred to as Catholic) was already present at the turn of the 9th and 10th centuries and in Poland at the end of the 11th (schools educating future members of the clergy). In Poland, the collapse of church education was marked by the communist system (1945–1989), and a dynamic revival was possible thanks to the democratic change in 1989. At present, Catholic schools, i.e., schools run by church legal entities and schools run by other legal or natural persons recognized as Catholic by decree of the diocesan bishop, entertain the same possibilities with respect to setup and operations on equal rights. Their number and proportion of the overall student population remain relatively stable. As the results published by District Examination Boards and rankings of Catholic schools show, the teaching efficiency of Catholic elementary schools is higher than average. High schools reach a very good level of education as well, although in their case, the dominance of Catholic schools is not in place. Teaching efficiency is one of many factors that influence the well-established position of Catholic schools.